Analisis Rasio Untuk Mengukur Kinerja Pada PT Bank Mandiri Persero Tbk (2015-2018) - Ressa Sasongko; Burhanuddin Burhanuddin; Rochmi Widayanti (JURNAL ILMIAH EDUNOMIKA, 2019)
Financial performance can demonstrate bank quality by going through the calculation of financial ratios The financial ratios of bank can be done by analyzing the financial statements published periodically. oaassess financial performanceain banking need to be aware of the analysis and cumulative financial impact. The purpose of this research is to determine the performance of Bank Mandiri listed at IDX using liquidity ratio, solvency and profitability in the years 2015-2018. The research methods in this study use descriptive research types. In this study the data used is secondary data, with Data collection. Technique that are documentation and library studies. From Bank Mandiri liquidity calculation, it shows good ratio or liquid. It can be seen from the current ratio, quick ratio, and cash ratio on Bank Mandiri's ability to meet the short term obligations have been made with good asset management, capital, and cash. The solvency of Bank Mandiri shows the ratio of good and solvable. It can be seen from the DAR and DER ratios that show declining year-to-year ratio. The profitability of Bank Mandiri shows fairly good ratio of figures despite the decline in 2016. Keywords: financial performance, financial ratios, analysis of financial statements